Characterization of optogenetically-induced cortical spreading depression in awake mice using graphene micro-transistor arrays. (6th April 2021) - Masvidal-Codina, Eduard; Smith, Trevor M; Rathore, Daman; Gao, Yunan; Illa, Xavi; Prats-Alfonso, Elisabet; Corro, Elena Del; Calia, Andrea Bonaccini; Rius, Gemma; Martin-Fernandez, Iñigo; Guger, Christoph; Reitner, Patrick; et al.
Abstract: Objective. The development of experimental methodology utilizing graphene micro-transistor arrays to facilitate and advance translational research into cortical spreading depression (CSD) in the awake brain. Approach. CSDs were reliably induced in awake nontransgenic mice using optogenetic methods. High-fidelity DC-coupled electrophysiological mapping of propagating CSDs was obtained using flexible arrays of graphene soultion-gated field-effect transistors (gSGFETs). Main results. Viral vectors targetted channelrhopsin expression in neurons of the motor cortex resulting in a transduction volume ⩾1 mm 3 . 5–10 s of continous blue light stimulation induced CSD that propagated across the cortex at a velocity of 3.0 ± 0.1 mm min −1 . Graphene micro-transistor arrays enabled high-density mapping of infraslow activity correlated with neuronal activity suppression across multiple frequency bands during both CSD initiation and propagation. Localized differences in the CSD waveform could be detected and categorized into distinct clusters demonstrating the spatial resolution advantages of DC-coupled recordings. We exploited the reliable and repeatable induction of CSDs using this preparation to perform proof-of-principle pharmacological interrogation studies using NMDA antagonists. MK801 (3 mg kg −1 ) suppressed CSD induction and propagation, an effect mirrored, albeit transiently, by ketamine (15 mg kg −1 ), thus demonstrating this models' applicability as a preclinical drug screening platform. Finally, we report that CSDs could be detected through the skull using graphene micro-transistors, highlighting additional advantages and future applications of this technology. Significance. CSD is thought to contribute to the pathophysiology of several neurological diseases. CSD research will benefit from technological advances that permit high density electrophysiological mapping of the CSD waveform and propagation across the cortex. We report an in vivo assay that permits minimally invasive optogenetic induction, combined with multichannel DC-coupled recordings enabled by gSGFETs in the awake brain. Adoption of this technological approach could facilitate and transform preclinical investigations of CSD in disease relevant models.